Study on Temporal and Spatial Evolution of Extreme Precipitation in Niululing Reservoir Basin of Hainan Province - XIAO Jing; MO Shuping; LIN Youwen; XIE Weining (Renmin Zhujiang)
According to the precipitation data of 11 rainfall stations from 1979 to 2020,the Mann-Kendall (MK) trend test,moving t-test,and wavelet analysis were used to analyze the spatial distribution,trend,abrupt changes,and periodicity of eight extreme precipitation indicators in Niululing Reservoir Basin.The results show that:①PRCPTOT,SDII,R50,and R100 in the basin gradually increase from upstream to downstream,and the spatial distribution of other indicators has no significant regularity.②The eight extreme precipitation indicators diverge in trend and fail the MK test.The PRCPTOT,CWD,R50,and R99PTOT show an increasing trend,while the other indicators show a decreasing trend.③The PRCPTOT,SDII,R50,and R100 in the basin had abrupt changes in 2008,and CWD,Rx1day,and Rx3day had abrupt changes in 1999,1998,and 2006,respectively.R99PTOT underwent abrupt changes in 1998 and 2015.④There are two or three periodic signals in the eight extreme precipitation indicators in the basin.Except R100 and R99PTOT,the average periods of the first and second periods of the other six extreme precipitation indicators are 19 a and 14 a,and those of R100 and R99PTOT are 10 a and 19 a.